2012 4th IEEE International Memory Workshop 2012
DOI: 10.1109/imw.2012.6213684
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cycling-Induced VT Instabilities in NAND Flash Cells via Compact Modeling

Abstract: Cycling-induced threshold-voltage instabilities in NAND Flash memory arrays are investigated via compact modeling of the NAND string. Calibration against experimental data allows the extraction of the model parameters and of their dependence on cycling dose and post-cycling bake time. Results are used to study the impact of charge trapping/detrapping in the tunnel oxide and interface state generation/annealing on the damage creation and recovery dynamics. It is shown that the former mechanism represents the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This value of activation energy had been also observed in earlier retention experiments [51]. Careful account of additional effects which may compromise a reliable extraction of E A , such as interface-state and mobility recovery [230,231] or disturbs [232], is required. The last data to be discussed relate to the cycling conditions dependence.…”
Section: Charge Detrappingsupporting
confidence: 69%
See 1 more Smart Citation
“…This value of activation energy had been also observed in earlier retention experiments [51]. Careful account of additional effects which may compromise a reliable extraction of E A , such as interface-state and mobility recovery [230,231] or disturbs [232], is required. The last data to be discussed relate to the cycling conditions dependence.…”
Section: Charge Detrappingsupporting
confidence: 69%
“…Interface state annealing manifests itself via a reduction of the activation energy, down from the 1.1 eV associated to detrapping to about 0.7 eV [230,231] or even 0.15 eV [249], and are also characterized by a non-uniform distribution over the cell area, usually peaked at the STI edges [74,250]. However, it has been suggested that their effect is dominant for high values of the read current only [230,231], while playing a minor role with respect to charge detrapping as the read current is reduced.…”
Section: Interface State Recoverymentioning
confidence: 99%
“…The characterization results evidenced that the phenomenon is unlikely ascribed only to a general V T instability that occurs in presence of stochastic charge trapping/de-trapping events in the tunnel-oxide/interface like for RTN [7], [18], [19] since the fail bits increase is localized in the first group of cells read (see Fig. 5).…”
Section: Discussion On the Tre Naturementioning
confidence: 95%